CTA's Selective Dissemination of Information (SDI) service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
CTA's Selective Dissemination of Information (SDI) serviceOne of the major constraints to agricultural research in the African, Caribbean and Pacific (ACP) countries, is access to current and relevant information in the form of primary documents,...